2012
DOI: 10.1007/s11655-012-1187-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain activity associated with memory and cognitive function during jaw-tapping movement in healthy subjects using functional magnetic resonance imaging

Abstract: Jaw-tapping movement might be a useful exercise for stimulating the memory and cognitive regions of the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…[ 21 ] The next steps were to hold the breath for a while and close the eyes, bump the teeth several times, and swallow as if saliva is stuck in the mouth – this was done to activate the brain and stimulate circulation to clears the mind and promote saliva secretion. [ 22 ] Finally, after 3 more rounds of Taesikbeop , the mind is stabilized, and the exercise is completed. LCE took 20 minutes per day 5 times a week for a total of 8 weeks (Table 2 and Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 21 ] The next steps were to hold the breath for a while and close the eyes, bump the teeth several times, and swallow as if saliva is stuck in the mouth – this was done to activate the brain and stimulate circulation to clears the mind and promote saliva secretion. [ 22 ] Finally, after 3 more rounds of Taesikbeop , the mind is stabilized, and the exercise is completed. LCE took 20 minutes per day 5 times a week for a total of 8 weeks (Table 2 and Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[16] We hypothesized that LCE will be effective, via respiratory meditation, in emotionally stabilizing patients as well as relieving symptoms by increasing diaphragmatic elevation and force, ventilation efficiency, thoracic movements, and sputum discharge. [17][18][19][20][21][22] This clinical trial was intended to determine the effects of LCE as a self-therapy and we anticipate that LCE is suitable for daily selftreatment, especially for older patients who have limitations with hospital visits. We used the 6-minute walk distance (6MWD), pulmonary function tests (PFTs), and several questionnaires as measured variables to evaluate exercise performance, symptoms, and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…We anticipate that LCE will be effective, via respiratory meditation, in emotionally stabilizing patients as well as symptomatically relieving symptoms by increasing diaphragmatic elevation and force, increasing ventilation efficiency, thoracic movements, and sputum discharge. [ 22 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] The next steps are to activate the brain and stimulate circulation that clears the mind and promotes saliva secretion. [ 27 ] Finally, after 3 more times of Taesikbub , the mind is stabilized, and the exercise is completed. LCE takes 20 minutes per day for 5 times a week and for a total of 8 weeks (Table 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…This method has been improvised by applying intraoral coins or chopsticks and used to cure headache, epilepsy, dizziness, tinnitus, sore throat, odontalgia, dislocation of the temporomandibular joint (TMJ), and other conditions 8 . A study conducted in 2013 showed that Gochi stimulated the memory and cognitive regions of the brain, as visualized on functional magnetic resonance imaging (fMRI) 9 …”
Section: Introductionmentioning
confidence: 99%